POTENSI TEPUNG TULANG BISON (BISON BISON) SEBAGAI ALTERNATIF BAHAN BAKU PAKAN TERNAK - ainun, ainun; Iryani, A. Sry (UIR Press, 2025)
Bison bone meal, a byproduct of the bison meat processing industry, has attracted attention as a source of minerals and protein for animal feed. A comprehensive analysis of the nutritional content of bison bone meal is needed to identify its specific advantages as a raw material for animal feed. This study aims to determine the potential of bison bone meal (Bison-bison) as an alternative raw material for animal feed. This study includes sample preparation, calcium analysis using the permanganatometry method, phosphorus analysis using the UV-Vis instrument, and nutritional content using the proximate method for water, ash, fat, and protein content parameters. Bison is a wild ruminant species known for its ability to adapt and survive in harsh environments. Bone meal is a feed raw material produced from animal processing waste. Bison bone meal has a significant mineral content, with a calcium (Ca) concentration ranging from 24-28% and phosphorus (P) 12-14%, creating a Ca:P ratio of around 2:1 which is ideal for animal nutrition. The content of bison bone meal is protein, fat, calcium and phosphorus. However, the main content of bison bone meal with the highest content is protein at 44.90%. The characterization carried out on bison bone meal is the analysis of water and ash content in bison bone meal with the results of the analysis of water content of 4.77% which is lower than the water content in beef bone meal. While the ash content is 37.69% and is greater when compared to beef bone meal. Based on SNI quality standards, each test parameter meets SNI standards. The addition of bison bone meal which is rich in protein and phosphorus to animal feed can improve the quality and productivity of livestock.